RANCANG BANGUN PEMESANAN TIKET BUS BERBASIS ONLINE: (STUDI KASUS AGEN PAHALA KENCANA BANYUWANGI) - Achmad Syauqi (Jurnal Ilmiah Informatika, 2018)
The intercity buses are vehicles that are designed to travel long distances. We must order tickets in advance according to the schedule offered. Usually by buying a ticket booking agent directly on the bus. Ticket sales system still uses many traditional systems in its service, bus ticket agents will record ticket reservations in books with a recording format that has been determined by their headquarters. Along with the rapid progress of time, then humans are required to follow developments, they need something simple, one of which is a matter of ordering bus tickets. This application is expected to help humans in bus ticket booking activities, which in this application humans do not need to come directly to the terminal or travel to order bus tickets, people just have to access this service. After that, users can open the web address of this application. This application will provide several menus that can be accessed by users, which also provides ease of ordering bus tickets. The design and implementation of Online Ticket Booking use the PHP programming language and MySQL database.